KEBIJAKAN PELAYANAN PENGURUSAN SERTIFIKAT TANAH ADAT DI KANTOR PERTANAHAN KOTA SORONG - Suaib, Muhammad Ridha (Universitas Muhammadiyah Sorong, 2017)
The community is the target of the policy, so it is to the public that the success of the policy should be asked. This study aims to describe the factors that become supporters and obstacles in the service policy of custom land certificate in the Land Office of Sorong City. This research uses descriptive approach of analysis, data collection technique by using interview, observation and documentation. The result of research indicates that the policy of service of land certificate in Sorong City Land Office is supporting factor in custom land certificate service, that is, the existence of file security from form filling, input, process, output and data guarantee, file security, with the prevailing rules, the absence of illegal levies, and fair service. The inhibiting factors in land certification services in the Land Office of Sorong City are the lack of simplicity in service, the lack of clarity and uncertainty in the service, not transparent in conveying information, and the lack of efficiency in the service